2022
DOI: 10.1186/s43066-022-00206-y
|View full text |Cite
|
Sign up to set email alerts
|

The regenerative effect of stem cells on acetaminophen-induced hepatotoxicity in male albino rats

Abstract: Background Acetaminophen overdose is the leading cause of acute liver injury (ALI) and acute liver failure (ALF) in the developed world. We aimed at studying the therapeutic potential of bone marrow mesenchymal stem cells (MSCs) in accelerating healing of acetaminophen-induced hepatotoxicity. Results This prospective study included 50 male albino rats divided into 2 groups: hepatotoxic group and non-hepatotoxic group. Hepatotoxicity was induced in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Changes in blood abnormalities were reported in acetaminophen poisoning since 1999. Recently, a study found the change in bone marrow stem cells (BMSCs) to be effective in improving liver damage caused by acetaminophen [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in blood abnormalities were reported in acetaminophen poisoning since 1999. Recently, a study found the change in bone marrow stem cells (BMSCs) to be effective in improving liver damage caused by acetaminophen [ 6 ].…”
Section: Introductionmentioning
confidence: 99%